The effect of fiscal policy on inflation volatility in Malawi - Nkuna, Bongekile (School of Economics, 2025)
The relationship between inflation and fiscal deficit has created a lot of interest among researchers; however, the results remain inconclusive. Malawi is a country that has rarely had stable inflation but at the same time fiscal policy has been one of the tools that has been constantly used to help the economy grow. The study thus examines the effect of government balance, the measure of fiscal policy used, on inflation volatility in Malawi from 1980 to 2022. Yearly inflation volatility is modelled using the Moving Average Standard Deviation methodology on monthly inflation data. An Autoregressive Distributed Lag (ARDL) process is used to find the long run relationship between inflation volatility and the fiscal variables while the Error Correction Model (ECM) is used to find the short run relationship. The results show that fiscal balance does have an impact on inflation volatility in both the long run and the short run. Results also show that the exchange rate has a significant impact but only in the short run.